RESPONS HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) TERHADAP PEMBERIAN BEBERAPA DOSIS KOMPOS BATANG PISANG DAN KONSENTRASI AIR CUCIAN BERAS - Sri Ritawati; Andi Apriany Fatmawaty; Arys Arys (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTThe research was determine yield response of tomato plants (Lycopersicum esculentum Mill.) to the giving of several doses of banana stem compost and theconcentration of rice washing water. This research was conducted in Pasir villageBinangun Waringin Kurung Serang Banten, with used Randomized CompletelyBlock Design as factorial with three repetation. The factor were examined included the compost banana stem: 20 ton ha-1 (60 g polybag-1); 25 ton ha-1 (75 g polybag-1); 30 ton ha-1 (90 g polybag-1), and a dose of rice water, namely: rice water 500 ml+500 ml of water; 750 ml rice water+250 ml of water; 1000 ml rice water. Parameters observed include: number of fruits per plant, fruit diameter and fruit weight per plant. The results showed that the dose of 25 ton ha-1 (75 g polybag-1) compost banana stem gave the best effect to the parameters of number of fruits per plant (4.85 fruits), fruit diameter (2.88 cm), and fruit weight plant-1 (87.51 g ). Provision of rice washing water concentration of 1000 ml of rice washing water tend gave better effect to parameter number of fruit plant-1 (4.24 fruit), fruit diameter (2.87 cm), and fruit weight plant-1 (85.10 g). However Between the use of compost banana stems and rice washing water interactions do not occured on the yield of tomato (Lycopersicum esculentum Mill.).